Análisis de la intención de emprendimiento en estudiantes universitarios de la Amazonía ecuatoriana - Manosalvas Vaca, Luis Oswaldo (2018)
Entrepreneurship has become a field of dynamic and differentiated research, where the entrepreneurship intentions have been considered as one of the antecedents of real entrepreneurship. The intentions are used to describe an individual prediction that allows to develop a fundamental behavior in the social, economic and human of the countries and regions. This research analyzes the entrepreneurial intention in university students from the Ecuadorian Amazon, considering that the Amazon region has an economic potential in development specifically tourism activity. In order to carry out this study, a quantitative research methodology was used, with descriptive and transversal analysis. Descriptive, inferential and multivariate statistical techniques were applied through a confirmatory factorial analysis and a relation structural equations SEM. The results showed that the subjective norm and entrepreneurial self-I Ecuador. efficacy dimensions are significantly related to the Entrepreneurship Intention, however, the Attitude does not have a significant influence on the Entrepreneurial Intention, these results allow to contribute in the development of business skills in the future entrepreneurs of the Amazon region.